A Problem Solving Approach to Group Employment Counselling - Borgen, William A.; Amundson, Norman E. (Revue canadienne de counseling et de psychothérapie, 1980)
It is becoming increasingly recognized that a group employment counselling approach presents many advantages in addressing some of the job readiness, job research and job search maintenance needs of clients. This article outlines a group problem solving model which can be applied in an employment counselling setting. There are seven stages in this model: (1) Identifying and sharing problems; (2) accepting responsibility for the problem; (3) accepting responsibility to do something about the problem; (4) stating the problem concretely; (5) exploring alternatives for resolving problems; (6) practising new behaviours; and, (7) group feedback and support. Each of the stages is described using related employment counselling examples.